Post traumatic anterior angulation of the distal tibia following malunion: A case report of management in a resource constrained setting - Dim, EM; Itie, JC; Inyang, UC; Nwashindi, A; Ugbeye, ME; Dim, UM (Asian Journal of Medical Sciences, 2014)
Fractures of the shaft of the tibia and fibula are common. Complications are minimal following careful application of principles during treatment by the Orthopaedic Surgeon. However, in our environment, not all patients present to the Orthopaedic Surgeon as they opt for some form of unconventional treatment, usually with the traditional bone setters. Such treatments sometimes lead to clinically unacceptable outcomes. This is a case report of a 42-year old female Nigerian with a 4-year history of post traumatic anterior angulation of the distal right tibia with severely contracted Achilles tendon following traditional bone setter’s treatment for open fractures of the distal tibia and fibula. There was 7 cm of right lower limb shortening and 45 degrees anterior angulation of a tibial malunion. She had a two- stage operation to correct the deformities. Patient achieved a plantigrade foot and fracture union without limb length discrepancy. DOI: http://dx.doi.org/10.3126/ajms.v6i1.10198 Asian Journal of Medical Sciences Vol.6(1) 2015 108-111